Analysis of social determinants with quality of life in people with HIV/AIDS at the voluntary counseling test clinic - Mulyanti; Dian Meiliani Yulis; Hairuddin K (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: HIV and AIDS are known to have become an emergency problem around the world, where infection transmission, morbidity rates, and mortality rates are still high. The existence of the HIV/AIDS epidemic is one of the scary scourges in the community because of its unexpected transmission by HIV due to human behavior. Objective: This study aims to analyze social determinants with quality of life in people with HIV/AIDS in the Voluntary Counseling and Testing Clinic. Methods: This study is an analytical study using a cross-sectional study research design. The population in this study is all HIV/AIDS patients domiciled in Kendari City. The sample consisted of 177 respondents, determined by simple random sampling. Data analysis uses the chi-square test and the multiple logistics test. Result: The results of the study showed that there was a stigma relationship with Odhiv's quality of life at the VCT Clinic of Kendari City Hospital (p = 0.000) and there was a relationship between social support and Odhiv's quality of life at the VCT Clinic of Kendari City Hospital (p = 0.000). The variable that has the greatest influence on the quality of life of ODHIV is the social support variable with an OR of 0.353. Conclusion: The variable that has the greatest influence on the quality of life of People with HIV/AIDS (ODHIV) is social support. Social support has proven to be a very significant factor in improving the quality of life of people living with HIV. Individuals with strong social support, whether from family, friends, or the community, tend to have a better quality of life than those who receive less social support. Social support plays a role in helping people with HIV cope with stigma, reduce psychological pressure, and provide a sense of security and comfort that can have a positive impact on their physical and mental well-being.